"As if possessing but one mouth": How Irenaeus Christianizes Classical Harmonia. Issue 2 (May 2022) - Franicevich, Jack
John Behr has noticed that Irenaeus uses the terms "harmony" and "symphony" to describe both God's action in salvation and the Church's action in right proclamation. However, Irenaeus does a great deal more with "harmony" than this. This paper argues that Irenaeus' discussion of harmony both corresponds to and christianizes the classical notion of harmonia along three lines: cosmological harmony, mythological harmony, and literary harmony. The paper begins by demonstrating the relationship between these three lines in classical thought, paying special attention to Plato and Quintillian. Then, it demonstrates the relationship between these three lines in Against Heresies. In a third section, it argues that Irenaeus' use of classical harmonia christianizes the notion along all three lines.